O conceito de imortalidade do homem na filosofia de Charles Sanders Peirce - Almeida, Rodrigo Vieira de (2016)
This doctorate research presents and defends the thesis that Charles Sanders Peirce’s philosophy has a place for a sui generis concept of man’s immortality within his scientific metaphysics. This concept of immortality, which may be briefly defined as the possibility of permanence of the influence of a man’s character, even after the dissolution of his body, i.e., even after his death, ultimately implies that death does not necessarily mean absolute discontinuity of the continuum that is man. It is, thus, a concept of immortality deeply ingrained in Synechism and, hence, in the author’s Realism and Objective Idealism, notwithstanding having also a relationship of a conjectural nature with his conception of the reality of God. We propose, therefore, to analyze how such a concept may be developed and effectively grounded within the author’s philosophical architecture